Case report of a pancreatic insulinoma misdiagnosed as epilepsy. Issue 5 (19th May 2021) - Williams, Barbara Anna; Lampart, Simon; Metzger, Jürg; Fischli, Stefan
Abstract : A 55-year-old patient had spent 12 years with unexplained seizures, initially diagnosed as epilepsy and then as a psychiatric disorder. When she was admitted with hypoglycaemia, a fasting test was performed showing blood sugar levels as low as 1 mmol/L with symptoms of neuroglycopenia. Insulinoma was suspected and an MRI showed a large tumour in the tail region of the pancreas. A Dodecanetetraacetic acid-Tyr3-octreotate (DOTATATE) positron emission tomography CT indicated no malignancy and showed no signs of metastasis. The patient underwent surgery, leaving her asymptomatic.